Measurements with a PET Coincidence Setup Based on the PETA5 ASIC and FBK RGB-HD SiPMs - Schug, David; Gebhardt, Pierre; Weissler, Bjoern; Gross-Weege, Nicolas; Dey, Thomas; Schulz, Volkmar (2017 IEEE Nuclear Science Symposium and Medical Imaging Conference (NSS/MIC), 2017)
We present results obtained with a positron emission tomography (PET) coincidence setup provided by the group of Prof. Peter Fischer from the University of Heidelberg (Lehrstuhl für Schaltungstechnik und Simulation, Institut für Technische Informatik). The setup employs two facing detector blocks which are built from an LYSO matrix of 30 × 30 × 10mm 3 in size with a crystal pitch of 2.5 mm read out in a one-to-one readout scheme by FBK RGB-HD SiPMs with a SPAD size of 25 μm. Each SiPM channel is digitized by a single input channel of a PETA5 (Position-Energy-Timing ASIC). Four PETA5 chips, each with 36 input channels, are mounted on one of the ceramic detector PCBs which incorporate a liquid cooling maze. We used multiple 22 Na point sources for calibration and evaluation purposes. In the calibration and result extraction, all available channels were taken into account simultaneously. The time-to-digital-converter (TDC) bins were calibrated and the noise pedestal for each channel was determined. The energy was calibrated and corrected for saturation using the 511 keV and the 1275 keV peaks, that were identified in the noise-pedestal-corrected ADC-value spectrum. Time offsets of all readout crystals were calibrated using coincident and qualified singles. The distribution of the TDC bin sizes was evaluated to have a mean of 50.2 ps and a standard deviation of approximately 20.2 ps. We determined the energy resolution of the setup for qualified coincidences as 13.0% and the coincidence resolution time as approximately 310 ps.